Enabling Stakeholder Decision-Making With Earth Observation and Modeling Data Using Tethys Platform - Nelson, E. James; Pulla, Sarva T.; Matin, Mir A.; Shakya, Kiran; Jones, Norm; Ames, Daniel P.; Ellenburg, W. Lee; Markert, Kel N.; David, Cédric H.; Zaitchik, Benjamin F.; Gatlin, Patrick; Hales, Riley (Frontiers in Environmental Science, 2019)
Tethys Platform is an open source framework for developing web-based applications for Earth Observation data. Our experience shows that Tethys significantly lowers the barrier for cloud-based app development, simplifies the process of accessing scalable distributed cloud computing resources and leverages additional software for data and computationally intensive modelling. The Tethys software development kit allows users to create web apps for visualizing, analyzing and modelling Earth Observation data. Tethys platform provides a collaborative environment for scientists to develop and deploy several Earth Observation web applications across multiple Tethys portals. We work in partnership with leading regional organizations world-wide to help developing countries use information provided by earth-observing satellites and geospatial technologies for managing climate risks and land use. This paper highlights the several Tethys portals and web applications that were developed as part of this effort. Implementation of the Tethys framework has significantly improved the Application Readiness Level metric for several NASA projects and the potential impact of Tethys to replicate and scale other applied science programs.